The clinico-radiological spectrum of masseteric venous malformation: Case report - Kavita Agarwal; Hemant R. Umarji; Sonali Kadam; Neeraj Agrawal (Journal of Oral Biology and Craniofacial Research)
Due to its location, intra-masseteric venous malformation often mistaken for a parotid swelling and clinical examination alone frequently underestimates the deep extension of the lesion and rarely gives accurate pre-operative diagnosis. But once it is diagnosed, the feasibility of the treatment and the plan of approach depend on accurate delineation of the extent, size and location of the lesion. Therefore, complimentary radiographic studies are essential for its management. In this case report, typical features of venous malformation within the masseter muscle, including clinical findings (turkey wattle sign) and imaging are presented. Ultrasonography and CT scan were non-contributory in the diagnosis, while on MRI, masseteric venous malformations have a typical appearance that allowed early identification, patient education and its management.